DiabCare Asia 2012: diabetes management, control, and complications in patients with type 2 diabetes in Indonesia (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Indonesia was a part of the most recent edition of DiabCare Asia held in 2008. DiabCare Asia 2012 is modeled after a similar project to provide the latest information to facilitate healthcare policymaking in this area. METHODS This was an observational, non-interventional, cross-sectional study of patients with type 2 diabetes mellitus from primary, secondary, and tertiary care centers in Indonesia. Patient data collected included demography, medical history complications, eye and foot examinations, diabetes management, and most recent laboratory investigations. Blood samples were collected from all patients for the analysis of glycated hemoglobin (HbA1c). RESULTS A total of 1,967 patients participated in the study, with a mean (SD) age of 58.4 (9.5) years and a median (range) duration of diabetes 6.0 (0.1−47.0) years. The percentage of patients with HbA1c <7.0% was 30.8% and the mean (SD) HbA1c level was 8.3 (2.2%). The proportion of patients using insulin was 34.7% with a mean (SD) total daily dose of 37.9 (24.1) IU. The most common diabetes-related complications were peripheral neuropathy (59.1%), erectile dysfunction (32.4%), and eye complications (29.1%). CONCLUSIONS Glycemic and metabolic control remain unsatisfactory in type 2 diabetes patients in Indonesia. Efforts are needed to optimize control and prevent complications in these patients.